FENOMENA PERILAKU BULLYING PADA REMAJA - Rika Kurniawati; Qarsela Tiara Umardi, Citra Finky Lestary, Risma Anita Puriani, Rizki Novirson (ADISAM PUBLISHER, 2025)
The purpose of this study is to provide an overview of bullying behaviour in adolescents. The method used in this research is the literature review method which raises the theme of bullying behaviour with the research subject being adolescents. The research was conducted by collecting and identifying journals in 2020-2024. The results showed that bullying behaviour in adolescents is caused by various factors, the most dominant of which is verbal bullying carried out by adolescents such as: mocking, cheering, making jokes that cause victims of bullying to decrease their level of confidence, become shy, and have an impact on the psychology of victims of bullying. Bullying behaviour that currently occurs is very high, so the need for proper education about the impact of bullying and the formation of empathy and mutual respect in the school environment is an important step in prevention efforts. Cooperation from all parties is needed so that bullying cases can prevent bullying in adolescents. The benefit of this research is that readers can see a picture of bullying behaviour in adolescents in the range of 2020-2024 and become an insight for guidance and counselling teachers regarding the various impacts of bullying that occur in adolescents.